Prevalence of Metabolic Syndrome in Women After Maternal Complications of Pregnancy: An Observational Cohort Analysis - Aldridge, Emily; Pathirana, Maleesa; Wittwer, Melanie; Sierp, Susan; Leemaqz, Shalem Y.; Roberts, Claire T.; Dekker, Gustaaf A.; Arstall, Margaret A. (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Certain complications of pregnancy, including hypertensive disorders of pregnancy, gestational diabetes mellitus, intrauterine growth restriction, spontaneous preterm birth, and placental abruption, are established independent risk factors for premature cardiovascular disease in women. Metabolic syndrome, which is associated with an increased risk of cardiovascular disease, may be a suitable alternative to traditional cardiovascular risk calculators that underestimate risk in young women. This study aimed to investigate the prevalence of metabolic syndrome in women who experienced a complicated pregnancy six months earlier. Methods: This observational study investigated the prevalence of metabolic syndrome as defined by the International Diabetes Federation in all eligible participants (n=247) attending a postpartum lifestyle intervention clinic from August 2018 to June 2021 at the Lyell McEwin Hospital in Adelaide, South Australia. Results: A total of 89 (36%) participants met the criteria for metabolic syndrome at a mean follow up time of seven months postpartum. Almost 90% of the cohort were abdominally obese, and over two thirds of the total cohort met at least two of the criteria for metabolic syndrome. Conclusions: Women with a prior history of one of the common major pregnancy complications are at high risk of future cardiovascular and metabolic disease, with many showing either metabolic syndrome or multiple risk factors at only seven months postpartum. The results indicate that follow-up within one year postpartum is an appropriate time to commence preventative strategies, as many women are already showing early signs of disease.